Organic Anion and Cation SLC22 “Drug” Transporter (Oat1, Oat3, and Oct1) Regulation during Development and Maturation of the Kidney Proximal Tubule - Gallegos, Thomas F.; Martovetsky, Gleb; Kouznetsova, Valentina; Bush, Kevin T.; Nigam, Sanjay K. (PLOS ONE, 2012)
Proper physiological function in the pre- and post-natal proximal tubule of the kidney depends upon the acquisition of selective permeability, apical-basolateral epithelial polarity and the expression of key transporters, including those involved in metabolite, toxin and drug handling. Particularly important are the SLC22 family of transporters, including the organic anion transporters Oat1 (originally identified as NKT) and Oat3 as well as the organic cation transporter Oct1. In ex vivo cultures of metanephric mesenchyme (MM; the embryonic progenitor tissue of the nephron) Oat function was evident before completion of nephron segmentation and corresponded with the maturation of tight junctions as measured biochemically by detergent extractability of the tight junction protein, ZO-1. Examination of available time series microarray data sets in the context of development and differentiation of the proximal tubule (derived from both in vivo and in vitro/ex vivo developing nephrons) allowed for correlation of gene expression data to biochemically and functionally defined states of development. This bioinformatic analysis yielded a network of genes with connectivity biased toward Hnf4α (but including Hnf1α, hyaluronic acid-CD44, and notch pathways). Intriguingly, the Oat1 and Oat3 genes were found to have strong temporal co-expression with Hnf4α in the cultured MM supporting the notion of some connection between the transporters and this transcription factor. Taken together with the ChIP-qPCR finding that Hnf4α occupies Oat1, Oat3, and Oct1 proximal promoters in the in vivo differentiating rat kidney, the data suggest a network of genes with Hnf4α at its center plays a role in regulating the terminal differentiation and capacity for drug and toxin handling by the nascent proximal tubule of the kidney.